2013
DOI: 10.1371/journal.pone.0068356
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Stress Granule Components That Are Involved in Nuclear Transport

Abstract: BackgroundImportin-α1 belongs to a subfamily of nuclear transport adaptors and participates in diverse cellular functions. Best understood for its role in protein transport, importin-α1 also contributes to other biological processes. For instance, arsenite treatment causes importin-α1 to associate with cytoplasmic stress granules (SGs) in mammalian cells. These stress-induced compartments contain translationally arrested mRNAs, small ribosomal subunits and numerous proteins involved in mRNA transport and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 59 publications
4
46
0
Order By: Relevance
“…Chang and Tarn observed that endogenous Transportin‐1 is present in P‐bodies and migrates into SGs when HeLa cells are exposed to various stresses. Importin‐β and its adaptors Importin‐α1, ‐α4 and –α5 [97–99] as well as Transportin‐2B, but not ‐2A (our own unpublished observations), also localize into SGs induced by diverse experimental conditions. This property is nevertheless not shared by all karyopherins.…”
Section: Potential Roles Of Tranportin‐1 and ‐2 Beyond Protein Nucleamentioning
confidence: 79%
“…Chang and Tarn observed that endogenous Transportin‐1 is present in P‐bodies and migrates into SGs when HeLa cells are exposed to various stresses. Importin‐β and its adaptors Importin‐α1, ‐α4 and –α5 [97–99] as well as Transportin‐2B, but not ‐2A (our own unpublished observations), also localize into SGs induced by diverse experimental conditions. This property is nevertheless not shared by all karyopherins.…”
Section: Potential Roles Of Tranportin‐1 and ‐2 Beyond Protein Nucleamentioning
confidence: 79%
“…107,108) Furthermore, knocking down importin α (KPNA2) delayed SG formation upon exposure to arsenite, implying its novel regulatory role in the process of SG assembly. 107) …”
Section: Stress Granulesmentioning
confidence: 99%
“…Crude cell extracts prepared for HeLa or MCF7 cells were probed side-by-side with primary antibodies and identical concentrations of isotype control IgG (Fig. S1) as previously described [41]. Primary antibodies against CAS, HuR, nucleolin or nucleostemin and fluorescently tagged secondary antibodies were further evaluated by fluorescence microscopy (Fig.…”
Section: Methodsmentioning
confidence: 99%